Formation of a Pension Allowance system for Civil Servants of the Tobolsk Province of the 19th - early 20th Centuries - L. N. Suslova (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The article is devoted to the study of historical experience in the formation of pensions for employees of the Tobolsk province in the XIX - early XX centuries. The authors of the article associate their interest in the indicated problems with its poor knowledge, as well as the reform of pension provision in modern Russia. The source of the study was the legislative, clerical and statistical documents of the funds of the School Directorate, City Council, Tobolsk Provincial Board, Tobolsk State Chamber, Tobolsk Gymnasium, Tobolsk State Bank, Tobolsk Post and Telegraph Office, Tobolsk Notary Archive and others. The most significant of these are the lists of pensioners living in the Tobolsk province, the Tobolsk Treasury Chamber statements on pensioners, documents that fix the number and size of pensions issued and not issued, and cases regarding the assignment of pensions. The authors of the article note the absence in the period under review of a single pension provision practice for all social categories of the population. The author analyzes pension payments accrued to officials from the treasury, and funded payments from public emmeritial cash desks. It is concluded that the formation of the pension provision of civil servants can be attributed to the end of the first quarter of the XIX century. The circle of persons entitled to receive a pension is designated, the sources of pension financing are identified. It was concluded that for the provision of pensions to officials of the period under review, the dependence of the pension salary on the size of the annual salary, the rank and length of service of the civil service was characteristic.